2018
DOI: 10.1002/chem.201800305
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Devices in the Fast‐Growing Domain of Single‐Cell Analysis

Abstract: Recent advances in cellular analysis revealed that the seemingly identical cells are heterogeneous in term of functionality, compositions, and genetic performance. These differences cause difficulty in the diagnostic for a specific model of disease. Detection of biomolecules such as DNA, RNA, and protein or analysis of cell(s), detection of cell surface molecules, and secreted protein, can help us to improve the understanding of a targeted disease and development of new diagnostic and therapeutic approaches. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 263 publications
(394 reference statements)
0
18
0
Order By: Relevance
“…In some cases, where cell viability is desired, this is a drawback; in other cases, this can be a feature: lysing a single cell and then immediately capturing its contents in a single droplet would facilitate single-cell resolution for a host of techniques, including single-cell sequencing, transcriptomics, and proteomics. [37][38][39] At present, these single-cell techniques, both in bulk and in droplets, rely on chemicals to break down the cell membrane or cell wall, lysing the cells and exposing their internal contents; 38,[40][41][42] how these chemical lysing agents affect genetic and protein materials is not in general known, 38 and at least in principle, a purely mechanical way to lyse cells and encapsulate their contents could be desirable.…”
Section: Simultaneous Cell Lysis and Encapsulationmentioning
confidence: 99%
“…In some cases, where cell viability is desired, this is a drawback; in other cases, this can be a feature: lysing a single cell and then immediately capturing its contents in a single droplet would facilitate single-cell resolution for a host of techniques, including single-cell sequencing, transcriptomics, and proteomics. [37][38][39] At present, these single-cell techniques, both in bulk and in droplets, rely on chemicals to break down the cell membrane or cell wall, lysing the cells and exposing their internal contents; 38,[40][41][42] how these chemical lysing agents affect genetic and protein materials is not in general known, 38 and at least in principle, a purely mechanical way to lyse cells and encapsulate their contents could be desirable.…”
Section: Simultaneous Cell Lysis and Encapsulationmentioning
confidence: 99%
“…In this paper, we present a novel enzyme-free approach for mechanically dissociating of tissue samples into viable single-cell suspensions. Liver is generally considered to be among the easiest tissues to dissociate, but hepatocytes are well known to be fragile [5]. Therefore this method is suitable, in particular as a model system, to prove the gentle tissue dissociation of an enzyme-free approach.…”
Section: Discussionmentioning
confidence: 99%
“…Single cell analysis requires effective, sensitive, and quantitative techniques for separation and detection [5]. Therefore, a desired tissue dissociation system is robust enough to effectively singularise the tissue while maintaining cell viability and cell yield.…”
Section: Tissue Grindermentioning
confidence: 99%
See 1 more Smart Citation
“…In concerning chip-MS system, Lin's group has designed an on-chip intestine-liver model for multiple drug absorption and metabolism behavior simulation. 56 In addition, Lin et al [57][58][59] have reported some other work on single-cell analysis, and have written a number of reviews in this field. In the past few years, various new chemical entities (NCEs) and screenable drug targets emerged quickly.…”
Section: •4 Analysis Of Metabolite and Metabolomementioning
confidence: 99%